Pengaruh Pakan Dan Tempat Pemeliharaan Yang Berbeda Terhadap Masa Perkembangan Larva Attacus atlas (L.) (Lepidoptera: Saturniidae) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The objective of this research is to determine the effects of different kinds of food on the developmental period of Attacus atlas (L.) larvae reared indoor and outdoor. The experimental design was The Completely Randomized Design with 2X3X4 factorial pattern. The first factor was the kind of food, i.e.: natural food (fresh leaves) for ird to 6th ins tar, and artificial diet for 16t to 3rd ins tar then shifted to fresh leaves for 4th to 6th instar. The second factor was the kind of plant fodder, i.e.: poncosudo (Nathopanax quincifolia), keben (Baringtonia asiatica), and sirsak (Annona muricata). The third factor was the rearing site, i.e.: indoor rearing for 1p1 to 6th instar, and indoor rearing for 1st to 3rd instar then shifted to outdoor rearing for 4th to 6th instar. There were twelve combinations of the whole treatments. Those larvae fed with the keben leaves and reared indoor for 1E4 to 6th instar had the shortest larval period with the average of 28_69(Â±0.712) days. The longest developmental period was found on those of larvae fed with artificial diet containing poncosudo leaf powder and reared indoor for 16t to 3rd instar then shifted to outdoor rearing for 4th to 6th instar with the average of 37.18(Â±1.160) days. Those larvae fed with the keben leaves and reared indoor for 1f4 to 3rd then shifted to outdoor rearing for 4th to 6th instar also gave the best cocoon quality